Interdisciplinary Perspectives on E-Scooters: A Bibliometric and Systematic Analysis of the Current Research - Yurdakul, Gokhan; Aydin, Nezir; Olanrewaju, Oludolapo Akanni (WILEY, 2025)
Since the integration of private vehicles into modern societies, traffic congestion has emerged as a critical and persistent problem. In recent years, the rise of micro-mobility, including all forms of light electric vehicles such as e-scooters and e-bikes, has introduced both innovative solutions and significant challenges. While many scholars argue that micro-mobility can help alleviate traffic-related issues, ongoing debates highlight potential drawbacks, including regulatory gaps, concerns over battery reliability, and the increased risk of severe injuries in accidents. Within this context, a systematic synthesis of the literature represents an important milestone for the field. This study systematically reviews academic research on electric scooters (e-scooters) published in journals indexed in SCI, SCI-Expanded, and SSCI, providing a comprehensive assessment of the existing body of literature. The review organizes the literature into eight thematic categories: demand forecasting, optimization, marketing, urban micro-mobility policies and user behaviour, health and safety, prior review studies, survey-based research, and other miscellaneous domains. From an initial pool of 1921 peer-reviewed articles, the application of objective filtering criteria produced a final dataset of 313 studies, each of which was rigorously examined and categorized accordingly. Using bibliometric techniques, the study analyses publication trends, the geographical distribution of research, collaboration networks among authors, and citation patterns within the e-scooter literature. The findings reveal that demand forecasting and optimization dominate in terms of publication volume, while health, safety, and legal/regulatory research remain comparatively underexplored. Bibliometric results further demonstrate a sharp increase in scholarly activity over the past 5 years, with the majority of studies concentrated in Europe, North America, and Asia. By identifying gaps in the existing literature and outlining priority areas for future research, this study provides both a synthesized knowledge base and practical insights for policymakers, urban planners, and industry stakeholders. The integrative perspective adopted here not only bridges disciplinary divides but also offers actionable recommendations for advancing e-scooter systems toward greater safety, inclusivity, and sustainability.
Keywords: electric vehicles; emission; environmental; emissions; air quality; intelligent transportation systems; other; public transport; road safety; smart cities; transportation; PHASE-CHANGE MATERIAL; ELECTRIC SCOOTERS; THERMAL MANAGEMENT; USAGE PATTERNS; MULTIPLE TYPES; ION BATTERY; MOBILITY; STATIONS; DESIGN; OPTIMIZATION; Engineering